PENGARUH PEMBERIAN UPAH DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS TENAGA KERJA PT DUTA TRANS JAYA JAKARTA - Rahmat Hidayat (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2018)
Organizational performance is the end result of the work done to achieve organizational goals that have been established. All that is determined by the existence of good labor productivity. There are several things that affect the productivity of labor, including the provision of wages and discipline work. One way to reward and acknowledge the existence of manpower is through the provision of wages. In addition to wage factors, labor productivity can also be influenced by work discipline factors. This study aims to determine the effect of wages and discipline of work on the productivity of labor at the company's Duta Trans Jaya Jakarta. The population of the research ani there are 40 employees, so researcher uses saturated samples by using all the popolation. So the sample in this study is 40 people. Based on the above data it can be seen that the value for wage variables, and work discipline (simultaneously) has a significant effect on work productivity, where the significant value of F of 0.000 <0.05 so it can be concluded that Ha accepted and Ho rejected this means that there is A significant influence between wage and work discipline variables on work productivity at PT. Duta Trans Jaya Jakarta.Â Kata kunci:Provision of Wage, Discipline Work, Productivity of worker